Macro-modelling of orthotropic damage in masonry: Combining micro-mechanics and continuum FE analysis. (November 2022) - Drougkas, Anastasios
Highlights: An efficient homogenisation scheme is proposed and validated. Orthotropic properties of masonry are calculated from its isotropic constituents. Stresses and strains in joints and units are calculated from macroscopic strain. Damage due to mechanical action on the joints and units can be simply quantified.